A review of pathogenic airborne fungi and bacteria: unveiling occurrence, sources, and profound human health implication - Al-Shaarani, Amran A. Q. A.; Pecoraro, Lorenzo (Frontiers in Microbiology, 2024)
Airborne fungi and bacteria have been extensively studied by researchers due to their significant effects on human health. We provided an overview of the distribution and sources of airborne pathogenic microbes, and a detailed description of the detrimental effects that these microorganisms cause to human health in both outdoor and indoor environments. By analyzing the large body of literature published in this field, we offered valuable insights into how airborne microbes influence our well-being. The findings highlight the harmful consequences associated with the exposure to airborne fungi and bacteria in a variety of natural and human-mediated environments. Certain demographic groups, including children and the elderly, immunocompromised individuals, and various categories of workers are particularly exposed and vulnerable to the detrimental effect on health of air microbial pollution. A number of studies performed up to date consistently identified Alternaria, Cladosporium, Penicillium, Aspergillus, and Fusarium as the predominant fungal genera in various indoor and outdoor environments. Among bacteria, Bacillus, Streptococcus, Micrococcus, Enterococcus, and Pseudomonas emerged as the dominant genera in air samples collected from numerous environments. All these findings contributed to expanding our knowledge on airborne microbe distribution, emphasizing the crucial need for further research and increased public awareness. Collectively, these efforts may play a vital role in safeguarding human health in the face of risks posed by airborne microbial contaminants.